2021
DOI: 10.4187/respcare.08948
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Bubble CPAP System for Low Resource Settings

Abstract: BACKGROUND: Despite its established safety, efficacy, and relative simplicity, CPAP treatment is not widely available for newborns and infants in low-and middle-income settings. A novel bubble CPAP system was designed to address the gaps in quality and accessibility of existing CPAP systems by providing blended, humidified, and pressurized gases without the need for electricity, compressed air, or manual power. This was the first study that tested the performance of the system with a simulated patient model. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…A concern with the Vayu bCPAP Systems was occasional disconnection of the oxygen tubing from the blender at FiO2s greater than .60. (17) Upon further investigation it was found that oxygen tubing (Figure 1A) that had been reprocessed many times (distinguishable by exterior hardening/yellowing) became vulnerable to disconnection at higher FiO2s. Hose clamps were introduced as an interim measure to secure older oxygen tubing, and subsequently the material of the oxygen tubing was modified to increase the hardness (from ASTM D 2240 Shore A 70 hardness to 80 hardness).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A concern with the Vayu bCPAP Systems was occasional disconnection of the oxygen tubing from the blender at FiO2s greater than .60. (17) Upon further investigation it was found that oxygen tubing (Figure 1A) that had been reprocessed many times (distinguishable by exterior hardening/yellowing) became vulnerable to disconnection at higher FiO2s. Hose clamps were introduced as an interim measure to secure older oxygen tubing, and subsequently the material of the oxygen tubing was modified to increase the hardness (from ASTM D 2240 Shore A 70 hardness to 80 hardness).…”
Section: Discussionmentioning
confidence: 98%
“…(16) The novel Vayu bCPAP System was developed to overcome current barriers to scale, and to make high quality CPAP available for global access. (17) Vayu bCPAP Systems have been used for three years to treat neonates with RDS, pneumonia, COVID-19, and other causes of severe respiratory distress in 13 countries. The Vayu bCPAP System revolves around an innovative air/oxygen blender that supplies the circuit with oxygen enriched air.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other designs of bCPAP and Venturi-type blenders are currently in various stages of development. [26][27][28] Our circuit design is distinct in that it uses a RAM cannula for patient interface rather than nasal prongs resembling Hudson RCI ® products. Our team selected a RAM cannula because this type of interface is simple to secure on the patient's face and is likely to be more feasible in LMIC environments where nursing ratios for neonatal in-patient care are relatively high.…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, Mollazadeh-Moghaddam et al described a Venturi device that could deliver low flows of blended air/oxygen to thin tubing like nasal cannula ( 14 ). Similar Venturi devices have been used in CPAP systems before, but not for low flow infant nasal cannula oxygen therapy ( 15 , 16 ). The design of this Venturi device was improved and integrated into a circuit with a low resistance nasal cannula to create a complete system for delivery of blended air/ oxygen to infants and children up to age five (Vayu Global Health Innovations, Boston, MA, USA).…”
Section: Introductionmentioning
confidence: 99%